Gambaran Kadar Hemoglobin pada Remaja Putri yang Mengkonsumsi Tablet Tambah Darah (FE) - Deby Illahi (Journal of Ners and Midwifery, 2015)
One of the programs of the Blitar City Health Department, through field work on the Child and Adolescent Nutrition, is socialization and acculturation efforts iron tablet supplement (Fe) in all schools in Blitar. SMP Negeri 4 Blitar City is the only school that has successfully implemented a program which has been carried by the Blitar city Health Department for 5 consecutive years, lie in 2010 until now (2014). The purpose of this study is to describe the level of hemoglobin in young women who consumed iron supplementation (Fe) in SMP Negeri 4 Blitar City. The method is descriptive, research instruments such as questionnaires and Sahli hemoglobin. The population of young women at SMP Negeri 4 Blitar City are 438 respondents and the samples are 65 respondents using proportional stratified random sampling method. Data collection takes place in June 2012, known that the results of this study is normal, by 77% (50 girls), low by 14% (9 girls), and high by 9% (6 girls). The frequency, pattern, long drink, solvents, and activity are several factors that can affect hemoglobin levels. Beside of the results, there was hopefully an collaboration between SMP Negeri 4 Blitar City and Blitar city Health Department to get evaluation of hemoglobin levels of young women who consumed iron supplementation (Fe) in SMP Negeri 4 Blitar City.